2014
DOI: 10.1186/1471-2474-15-386
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced collagen type I synthesis by human tenocytes subjected to periodic in vitro mechanical stimulation

Abstract: BackgroundMechanical stimulation (e.g. slow heavy loading) has proven beneficial in the rehabilitation of chronic tendinopathy, however the optimal parameters of stimulation have not been experimentally determined. In this study of mechanically stimulated human tenocytes, the influence of rest insertion and cycle number on (1) the protein and mRNA levels of type I and III collagen; (2) the mRNA levels of transforming growth factor beta (TGFB1) and scleraxis (SCXA); and (3) tenocyte morphology, were assessed.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 39 publications
3
32
3
Order By: Relevance
“…Gene expression analysis of TCs indicate that the use of 10% strain and MMC can be conducive to tenogenic phenotype maintenance because SCXA was up‐regulated at d 7 and is typically considered a tenogenic marker. Contrary to our results, mechanical stimulation is commonly associated with increased COL1A1 synthesis in TCs (82, 99). Furthermore, expression of collagen type III, TNC, TNMD, and SCXA is also typically increased (32, 99, 100).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Gene expression analysis of TCs indicate that the use of 10% strain and MMC can be conducive to tenogenic phenotype maintenance because SCXA was up‐regulated at d 7 and is typically considered a tenogenic marker. Contrary to our results, mechanical stimulation is commonly associated with increased COL1A1 synthesis in TCs (82, 99). Furthermore, expression of collagen type III, TNC, TNMD, and SCXA is also typically increased (32, 99, 100).…”
Section: Resultscontrasting
confidence: 99%
“…The confined environment created by the high natural polydispersity of Cr in the culture medium accelerates cleavage of the N‐ and C ‐ propeptides of the procollagen molecules by the N‐ and C ‐ proteinases, thereby creating the insoluble collagen molecule (40, 41). COL1A1 was not increased at 10% strain, which contradicts previous studies in which mechanical stimulation led to increased COL1A1 synthesis in TCs (82, 8789) and BMSCs (30, 90, 91), a process mediated by TGF‐β1 (92). Increased deposition of collagen types III, IV, V, and VI has been observed in fibroblasts (41), and increased deposition of collagen III has been described in BMSCs (47) and corneal fibroblasts (42) when using Cr as a crowder.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…The ability of tendon to grow and respond to mechanical and biochemical cues requires the coordination of multiple biologic processes. Studies of 3‐dimensional tissue engineered tendon constructs in culture and exercise training in human subjects have shown that tendons grow best in response to intermittent mechanical loading with adequate rest periods built in between loading regimes (35, 61,62). Failure of tendons to respond to these cues can lead to the development of tendinopathies or tendon ruptures (8).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, fibroblasts need mechanical stimulation for alignment of the collagen fibrils and presumably also for the cells themselves, in a similar manner as osteocytes seem to align . Fibroblasts, in general, are indeed very sensitive to mechanical stimulation and under such conditions produce a wide variety of bioactive compounds, related to both matrix production (COL1, decorin, transforming growth factor‐beta1, scleraxis) and inflammation and remodeling (interleukin‐6, interleukin‐8, matrix metalloproteinase‐13) . Mechanical stimulation is thus an essential feature for the remodeling and production of the extracellular matrix of the PDL.…”
Section: Composition Structure and Organization Of The Mature Pdlmentioning
confidence: 99%